Interaction of two memory enhancing herbal drugs memory plus and mentat with morphine and imipramine in mice - Gupta, Neera R.; Patel, Varsha J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The non-medical self-administration of memory enhancing drugs is a common practice. Present study was designed to evaluate interactions of two such herbal drugs- Memory plus (MP) and Mentat, with other central nervous system active drugs. Methods: Two activities-analgesic activity and antidepressant activity were performed using adult albino mice of both sexes weighing 25-30g to observe the interactions of the herbal drugs with morphine and imipramine respectively. For each activity animals were divided into seven groups of six mice each. Group-I was control group receiving 0.2ml of 1% Tween 80 ip/ 0.2 ml saline p.o, Group II, III and IV acute treatment groups; received single dose of herbal (2mg/kg ip MP or 200mg/kg po Mentat) CNS active drugs alone in subeffective doses. Group II received morphine 2mg/kg ip, group III imipramine 2mg/kg ip and group IV-received MP/Mentat+ morphine or imipramine respectively. Groups V, VI and VII were subchronic treatment groups, received drugs once daily for eight days in same dose as acute treatment groups II, III and IV respectively. Analgesic activity was measured as prolongation of reaction time by hot plate method and antidepressant activity by reduction in despair time using Porsolt’s forced swimming test. Results: When administered for 8 days, both MP and Mentat potentiated the effect of morphine preventing the development of tolerance to analgesic effect (P< 0.05). However the antidepressant effect of imipramine was not modified by any in subchronic treatment groups. Conclusions: Two herbal memory enhancing preparations Memory plus and Mentat potentiate analgesic effect of morphine but not the antidepressant action of imipramine in mice.